Modernism - Childs, Peter 1962- (Abingdon, Oxon, [England] Routledge, 2017)
"Modernist movements radically transformed the late nineteenth- and early twentieth-century literary establishment, and their effects are still felt today. Modernism introduces and analyzes what amounted to nothing less than a literary and cultural revolution. In this fully updated, expanded, and revised third edition, charting modernism in its global and local contexts, Peter Childs: - details the origins of modernism and the influence of thinkers such as Darwin, Marx, Freud, Nietzsche, Saussure and Einstein - explores the radical changes which occurred in the arts, literature, drama, and film of the period - traces 'modernism at work' in literature, especially in writings by a range of British, Irish, American and other Anglophone authors including James Joyce, Virginia Woolf, Samuel Beckett, Nella Larsen, Gertrude Stein, Katherine Mansfield, T. S. Eliot, and many others - explains recent critical interest in the culture and worldwide impact of modernism - reflects upon the shift from modernism to postmodernism. At once accessible and critically informed, Modernism guides readers from first steps in the field to an advanced understanding of one of the most important cultural phenomena of the last centuries."--Provided by publisher.
Introduction. Answering the question : what is modernism? -- Plunging in -- Words, words, words : modern, modernism, modernity -- Periods, genres, models -- International anglophone modernisms -- Cultures of modernism -- Interpreting and changing. Marx -- Darwin -- Freud -- Nietzsche -- Saussure -- Einstein -- Genres and the arts. Novel -- Short story -- Poetry -- Drama -- Art movements -- Film -- Photography, dance and music -- Texts, contexts, intertexts. 'The struggle of becoming' : freedom and gender -- 'It seems to me I am trying to tell you a dream ': epistemology and narration -- 'These fragments I have shored against my ruins' : identity and war -- 'Who's passing for who?' : sexual and racial divisions -- 'History is a nightmare' : symbolism and language.
Includes bibliographical references (pages [225]-233) and index.
Keywords: Modernism (Art); Arts, Modern -- 19th century; Arts, Modern -- 20th century